Factors affecting quality during the construction phase in Iraqi government companies - M. Ahmed, Husam; Mohd Yusuff, Rosnah (Research India Publications, 2016)
Construction projects play a significant part in the development of any country and quality is one of the important factors in the success of the construction industry. There is a lack of understanding of quality is the problem in the construction industry in Iraq, but the main problem is the absence of good quality supervision of the construction industry. Based on the literature review yielded managers, designers, and contractors with necessary information needed to better manage the quality of a construction project by identifying the factors that affect process quality of construction projects and to rank them by degree of importance and develop a model to represent the factors affecting the overall quality of Construction projects. This study was based on questionnaire surveys, which was designed based on literature review. After, validation a total 109 questionnaires were collected among project manager, quality engineer, and general manager in Baghdad, the capital city of Iraq. Data were analysed using descriptive statistics and multiple regression analysis applying SPSS software Ver.21. The results of data analysis indicated that the level of importance all factors were more than a moderate level and the highest level which was almost high belonged to the material. The other factors, including Quality systems, Owner, Design, Equipment, Labors and contractor almost ranged between 3.69-3.75. Based on multiple regression analysis among all factors only “contractor” did not show any significant effect on quality in construction projects. The highest effect belonged to, quality systems with (β=0.289, P value<0.001) and then owner and materials followed by design, equipment, site staff and the lowest impact was observed for labor factor (β=0.137, P value=0.049).